2012
DOI: 10.1080/1059924x.2012.658298
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Marketing to Address Barriers and Motivators to Agricultural Safety and Health Best Practices

Abstract: Social marketing is an intervention development strategy that pays considerable attention to barriers to and motivators for behavioral change or adoption of recommended behaviors. Barriers are obstacles that prevent individuals from changing or adopting behaviors and are often referred to as the "cons" or "costs" of doing something. Motivators, on the other hand, are factors that encourage individuals to change or adopt behaviors and are often referred to as the "pros," "benefits," or "influencing factors" of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The approach based on social marketing principles defines population segments, identifies their needs, develops intervention approaches responding to the needs, and delivers information using the most effective communication channels for each population segment. Data were collected by various methods to identify barriers and motivators leading toward healthier and safer farmers [21][22][23][24].…”
Section: Research Aimsmentioning
confidence: 99%
“…The approach based on social marketing principles defines population segments, identifies their needs, develops intervention approaches responding to the needs, and delivers information using the most effective communication channels for each population segment. Data were collected by various methods to identify barriers and motivators leading toward healthier and safer farmers [21][22][23][24].…”
Section: Research Aimsmentioning
confidence: 99%
“…This supports previous efforts in agriculture, which utilized targeted messages to address topics such as tractor overturns, aging farmers, and youth safety. [18][19]25 Small-group discussions with farmers indicated that the initial encounter with a message must be thought-provoking, as they have many things vying for their attention. These triad sentiments were similar to those identified in the concept testing of tractor safety messages in New York.…”
Section: Discussionmentioning
confidence: 99%
“…18, 19 A review by Gordon et al 16 concludes that social marketing methods can be applied to a wide range of target populations, settings, and topic areas. Within agriculture, social marketing efforts directed at youth safety initiatives and retrofitting tractors for rollover protective structures (ROPS) have proven successful.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations